Inflammation, depression, and anxiety disorder: A population-based study examining the association between Interleukin-6 and the experiencing of depressive and anxiety symptoms - LEE, Sean Teck Hao (Institutional Knowledge at Singapore Management University, 2020)
The uncovering of a positive association between inflammatory cytokine levels – Interkleukin-6 (IL-6) in particular – and the experiencing of depressive and anxiety symptoms is one of the most promising and enthusiastically-discussed finding in recent years. Despite considerable ambiguity in the directionality and underpinnings of this association, anti-inflammatory drugs are already being tested on mental health patients who present no physical symptoms of inflammation, risking potential adverse side effects. Researchers have thus urgently called for more rigorous empirical elucidations of this association. Based on a large, longitudinal, nationally representative sample of middle-aged adults in the United States (N = 1255), IL-6 was observed to be significantly associated with one's present experiencing of depressive and anxiety symptoms. However, IL-6 was predictive of only prospective depressive (not anxiety) symptoms measured six years later, and only when baseline number of symptoms was not accounted for. Further, evidence for IL-6’s postulated role as being either a biological cause itself (augmenting HPA stress reactivity) or a biological consequence of a psychological cause (psychological stress) for depression and anxiety was not found. These findings underscore the imperativeness of more rigorous studies to be conducted in this area, and caution practitioners against the premature consideration of IL-6 levels in clinical practice.